Effect of Different Methods of Zinc Application on Yield and Quality of Rabi Maize in West Tripura - Saurav Das; Goutam Kumar Ghosh; Debashish Sen (International Journal of Economic Plants)
The present study was conducted at Experimental Farm, College of Agriculture, Tripura with an aim to find out the effect of different methods of Zn application on maize crop during rabi season of 2018−19 (November−February). The experiment was laid out in Randomized block design (RBD) and replicated three times. In this experiment, zinc was applied by three methods- soil, foliar and their combinations. Zinc was applied @ 10, 20 and 30 kg ha-1 in soil during sowing, while foliar application @ 1% Zinc was given during silking stage. Zinc was applied in the form of Zinc Sulfate in all the treatments. Recommended dose of fertilizer for maize crop @ 150:70:70 kg N, P2O5 and K2O ha-1 were applied according to the treatment details. The application of zinc via soil and foliar @ 30 kg ha-1 and 1% ZnSO4 recorded higher yield parameters such as number of cobs plant-1, weight of cobs plant-1, number of grains cob-1, total weight of grains plant-1 and average 1000 grains weight etc. The increasing Zn rates also enhanced grain yield ha-1, grain harvest index and zinc uptake in plant and maize grains in significant manner.